The impact of soybean mosaic virus infection on biochemical composition of soybean seed - O. О. Molodchenkova; A. V. Dashchenko; I. A. Mishchenko; A. A. Dunich; I. I. Motsniy; P. S. Tykhonov; L. T. Mishchenko (The Ukrainian Biochemical Journal, 2025)
It is known that infection caused by soybean mosaic virus (SMV) has a negative effect on soybean yield, productivity and seed quality. The main indicators of the nutritional value of soybean seed are the content of main storage proteins glycinin and β-conglycinin, as well as flavonoids, carbohydrates and fat. The goal of the research was to study the impact of SMV infection on the biochemical composition of the seeds of the soybean varieties created by classical breeding methods (‘Kano’, ‘Kuban’, ‘Kordoba’) and varieties of transgenic soybean (‘Grimo’ and ‘Monro’). DAS-ELISA and two step RT-PCR were used to identify SMV. Protein electrophoresis was carried out in 15% polyacrylamide gel containing 0.1% SDS at pH 8.3 according to the Laemmli method. We detected an increase in the activity of trypsin inhibitor and lectins and a decrease flavonoids content in the infected seeds of studied varieties in comparison with the healthy seeds. Seeds of all infected varieties showed a decrease in glycinin content and glycinin/β-conglycinin ratio, with the exception of ‘Monroe’ infected seeds in which both glycinin and β-conglycinin contents were increased or at the level of healthy seeds. We can distinguish the variety ‘Kano’ with a high content of flavonoids, varieties ‘Kuban’ and ‘Grimo’ with increased or maintained levels of healthy seed content of carbohydrates, fat and proteins under infection conditions. The differences in the relative content of the components of β-conglycinin and glycinin subunits in infected seeds depending on the soybean variety were revealed. The obtained results can be used for the selection of soybean varieties resistant to viral infection and with high seed quality.